2009
DOI: 10.4149/neo_2009_04_317
|View full text |Cite
|
Sign up to set email alerts
|

17β-hydroxysteroid dehydrogenase type 11 (Pan1b) expression in human prostate cancer

Abstract: Androgens are reported to be actively produced in situ in human prostate cancer. These locally produced androgens are also demonstrated to play important role in the pathogenesis and development of human prostate cancer. The status of locally produced androgen inactivation and metabolism, however, remains unclear. Therefore, it is important to examine the status of this in situ androgen metabolism and inactivation in order to improve clinical response to endocrine therapy in the patients diagnosed with prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…: false discovery rate estimation by the Benjamini and Hochberg procedure [25]). Searching for evidence in PubMed for association between HSD17B11 and melanoma brings up no hits but is associated with seminal vesicle invasion in prostate cancer [26]. TranSMART system also enables doing a thorough search across multiple databases for evidence of a gene's involvement in biological processes and experiments as illustrated in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…: false discovery rate estimation by the Benjamini and Hochberg procedure [25]). Searching for evidence in PubMed for association between HSD17B11 and melanoma brings up no hits but is associated with seminal vesicle invasion in prostate cancer [26]. TranSMART system also enables doing a thorough search across multiple databases for evidence of a gene's involvement in biological processes and experiments as illustrated in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…HSD17B11 expression has been shown to be higher in PC relative to normal prostate cells (Nakamura et al 2009). To better understand the mechanisms that regulate HSD17B11 gene in PC, up to 2 Kb of the 5’-flanking region of the gene were cloned into a pGL3-Basic vector to form pB11-2016.…”
Section: Resultsmentioning
confidence: 99%
“…Since HSD17B11 converts 3α-Diol into androsterone thus reducing its intracellular levels, it is possible that this enzyme also contributes to progression to androgen independence in PC. Interestingly, HSD17B11 expression has been shown to be upregulated in human PC cells (Nakamura et al 2009). Here we show that mutation of the binding sites for C/EBPα and Sp1 decreases HSD17B11 promoter activity to less than 20% in PC cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations demonstrated that 17␤-HSD-11 can be up-regulated significantly by peroxisome proliferator-activated receptor (PPAR␣) agonists in mouse intestine, indicating that this enzyme is also involved in the lipid metabolic pathways of mouse [19][20][21]. 17␤-HSD-11 has a broad tissue distribution in humans as it was detected in the pancreas, kidney, liver, and lung as well as steroidogenic cells [17], and is also found in an androgen-dependent prostate cancer cell line [22,23].…”
Section: Introductionmentioning
confidence: 96%